HDAC6 inhibitor ACY1215 inhibits the activation of NLRP3 inflammasome in acute liver failure by regulating the ATM/F‐actin signalling pathway. Issue 15 (27th June 2021) - Chen, Qian; Wang, Yao; Jiao, Fangzhou; Cao, Pan; Shi, Chunxia; Pei, Maohua; Wang, Luwen; Gong, Zuojiong
Abstract: Acute liver failure (ALF) is a rare and critical medical condition. This study was designed to investigate the protective effects and underlying mechanism of ACY1215 in ALF mice. Our findings suggested that ACY1215 treatment ameliorates the pathological hepatic damage of ALF and decreases the serum levels of ALT and AST. Furthermore, ACY1215 pretreatment increased the level of ATM, γ‐H2AX, Chk2, p53, p21, F‐actin and vinculin in ALF. Moreover, ACY1215 inhibited the level of NLRP3, ASC, caspase‐1, IL‐1β and IL‐18 in ALF. The ATM inhibitor KU55933 could decrease the level of ATM, γ‐H2AX, Chk2, p53, p21, F‐actin and vinculin in ALF with ACY1215 pretreatment. The F‐actin inhibitor cytochalasin B decreased the level of F‐actin and vinculin in ALF with ACY1215 pretreatment. However, cytochalasin B had no effect on protein levels of ATM, Chk2, p53 and p21 in ALF with ACY1215 pretreatment. Cytochalasin B could dramatically increase the level of NLRP3, ASC, caspase‐1, IL‐1β and IL‐18 in ALF with ACY1215 pretreatment. These results indicated that ACY1215 exhibited hepatoprotective properties, which was associated with the inhibition of NLRP3 inflammasome, and this effect of ACY1215 was connected with upregulation of the ATM/F‐actin mediated signalling pathways.